Prediction versus understanding in computationally enhanced neuroscience. - Chirimuuta, M. (Synthese, 2021)
The use of machine learning instead of traditional models in neuroscience raises significant questions about the epistemic benefits of the newer methods. I draw on the literature on model intelligibility in the philosophy of science to offer some benchmarks for the interpretability of artificial neural networks (ANN's) used as a predictive tool in neuroscience. Following two case studies on the use of ANN's to model motor cortex and the visual system, I argue that the benefit of providing the scientist with understanding of the brain trades off against the predictive accuracy of the models. This trade-off between prediction and understanding is better explained by a non-factivist account of scientific understanding.